Maternal feeding styles in infancy predict child body mass index z-scores at 72 months: findings from a cohort of Jamaican children - Wright, Amika S.; Guthrie-Dixon, Natalie; Tulloch-Reid, Marshall K.; Chang, Susan M.; Walker, Susan P. (Frontiers in Public Health, 2023)
Objective To explore whether maternal feeding styles at 12 months predict child Body Mass Index (BMI) z-scores at 72 months and evaluate whether BMI z-scores at 18 months mediates the association. Methods Data from 239 mother–child pairs participating in a parenting intervention were analyzed. Feeding information was ascertained at 12 months by questionnaire with feeding styles identified using factor analysis. Children’s weight and length/height were measured at 18 and 72 months and BMI z-scores computed. Maternal sociodemographic data, depressive symptoms and language skills were obtained by questionnaire. Multilevel linear regression analysis was used to examine whether feeding styles predicted 72 month BMI z-scores. Complete case analysis was conducted and multiple imputation used to treat missing values of explanatory and outcome variables at 18 and 72 months. Mediational analysis was performed to assess the indirect effects of feeding styles on 72 month BMI z-scores via 18 month BMI z-scores. Results Restrictive feeding at age 12 months predicted higher 72 month BMI z-scores in both complete case analysis [β (95%CI): 0.19 (0.02, 0.37)] and multiple imputation [β (95%CI): 0.20 (0.02, 0.39)]. Uninvolved, forceful, indulgent and responsive feeding styles were not significant predictors of 72 month BMI z-scores. A significant indirect effect was observed between restrictive feeding and child BMI z-scores at 72 months via 18 month BMI z-scores [β (95% CI) 0.12 (0.03, 0.22)]. Conclusion Restrictive feeding at 12 months was associated with higher BMI z-scores at 72 months and appeared to be mediated by BMI z-scores at 18 months.